2012
DOI: 10.1111/j.1551-2916.2012.05368.x
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of 3D‐Printed Glass/HAp Composites

Abstract: We report the sintering of 3D‐printed composites of 13‐93 bioactive glass and hydroxyapatite (HAp) powders. The sintering process is characterized on conventionally produced powder compacts with varying HAp content. A numeric approximation of the densification kinetics is then obtained on the basis of Frenkel, Mackenzie–Shuttleworth, and Einstein–Roscoe models, and optimized sintering conditions for 3D‐printed structures are derived. Fully isotropic sintering of complex cellular composites is obtained by conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Received: January 16,2014 Final Version: February 27, 2014 C [284] ZrC [160] TiC/Ni [289] Al 2 O 3 -ZrO 2 [191] Polymer-derived ceramics: see present work Functional ceramics BaTiO 3 [40,41] PZT [89] PZT [211,223,239] BaTiO 3 [150] SiO 2 -Al 2 O 3 -RO-glass [269] PZT [37,[45][46][47] BaTiO 3 [115] SiCN [225] PZT [145,146] LZSA-Glass [272] TiO 2 [43,44] PMN [192] PZT [282] LSMO/YBCO [48] LiFePO 4 [170] Li 4 Ti 5 O 12 BaZrO 3 , SrTiO 3 , BaMn 2 Al 10 O 19À x [193] ITO [119] ZnO [119,187] La(Mg 0.5 , Ti 0.5 )O 3 [167,188] Zr 0.8 Sn 0.2 TiO 4 [188] TiO 2 [119] Bioceramics HA [50,66,67,[69][70][71][72] Apatite-Mullite [107][108]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Received: January 16,2014 Final Version: February 27, 2014 C [284] ZrC [160] TiC/Ni [289] Al 2 O 3 -ZrO 2 [191] Polymer-derived ceramics: see present work Functional ceramics BaTiO 3 [40,41] PZT [89] PZT [211,223,239] BaTiO 3 [150] SiO 2 -Al 2 O 3 -RO-glass [269] PZT [37,[45][46][47] BaTiO 3 [115] SiCN [225] PZT [145,146] LZSA-Glass [272] TiO 2 [43,44] PMN [192] PZT [282] LSMO/YBCO [48] LiFePO 4 [170] Li 4 Ti 5 O 12 BaZrO 3 , SrTiO 3 , BaMn 2 Al 10 O 19À x [193] ITO [119] ZnO [119,187] La(Mg 0.5 , Ti 0.5 )O 3 [167,188] Zr 0.8 Sn 0.2 TiO 4 [188] TiO 2 [119] Bioceramics HA [50,66,67,[69][70][71][72] Apatite-Mullite [107][108]…”
Section: Discussionmentioning
confidence: 99%
“…He quantified the optimal powder parameters such as the particle size (20-35 mm), compaction rate r Tapped /r Bulk (1.3-1.4), flowability ff c , defined as the ratio of consolidation stress s 1 and the compression strength s c (5-7), and powder bed surface roughness (10-25 mm). The need for at least one post-processing step (cold-isostatic pressing, [61] infiltration with preceramic polymers [62,63] or liquid metals, [51,64] chemical vapor infiltration, [65] and sintering [66,67] ) reduces the productivity of three-dimensional printing methods, so several approaches exist to increase the green density. It was observed that implementation of binder-coated particles effectively improves the green and sintered strengths.…”
Section: Three-dimensional Printing (3dp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Large and complex structures may significantly deform because of a number of factors, such as gravity, intrinsic strain or temperature, surface tension and density gradients. 10 Such effects seen during the sintering of glass materials can be minimised by reducing the glass fraction of the composite materials. Winkel et al (2012) developed bioactive glass composites with HA powder to fabricate 3D scaffolds.…”
Section: D Printable Composite Materials For Biomedical Applicationsmentioning
confidence: 99%
“…7 Running parallel to these technological developments, there has also been rapidly growing interest in the preblending of materials and/or the inclusion of 'fillers' into printable resins, which deliver distinct physicochemical properties into the resultant materials, thus producing 3D printed composites which exhibit unique characteristics and capabilities. [8][9][10][11][12][13][14][15] Indeed, in the area of composite design and production, 3D printing represents a technology with immense potential, again providing low cost, simple and rapid prototyping advantages over traditional methods for fabrication of composite materials and objects. rication methods, applications, advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%